A Herpesviral induction of RAE-1 NKG2D ligand expression occurs through release of HDAC mediated repression - Greene, Trever T; Tokuyama, Maria; Knudsen, Giselle M; Kunz, Michele; Lin, James; Greninger, Alexander L; DeFilippis, Victor R; DeRisi, Joseph L; Raulet, David H; Coscoy, Laurent (eLife, 2016)
Natural Killer (NK) cells are essential for control of viral infection and cancer. NK cells express NKG2D, an activating receptor that directly recognizes NKG2D ligands. These are expressed at low level on healthy cells, but are induced by stresses like infection and transformation. The physiological events that drive NKG2D ligand expression during infection are still poorly understood. We observed that the mouse cytomegalovirus encoded protein m18 is necessary and sufficient to drive expression of the RAE-1 family of NKG2D ligands. We demonstrate that RAE-1 is transcriptionally repressed by histone deacetylase inhibitor 3 (HDAC3) in healthy cells, and m18 relieves this repression by directly interacting with Casein Kinase II and preventing it from activating HDAC3. Accordingly, we found that HDAC inhibiting proteins from human herpesviruses induce human NKG2D ligand ULBP-1. Thus our findings indicate that virally mediated HDAC inhibition can act as a signal for the host to activate NK-cell recognition.
Keywords: NK cells; NKG2D; histone deacetylase; herpesviruses; NKG2D ligands; CK2